A study on the factors influence growth of Islamic banking and finance products in Malaysia / Nurhafiza Mohd Nasri - Mohd Nasri, Nurhafiza (Faculty of Business and Management, 2011)
Islamic banking could be referring to as the banking system that is in line with the shariah principles or Islamic law and through the development of Islamic economics; it is suitable and practical to be applied in day to day business activities. It is well known that, shariah principles was strongly prohibited the usage of Riba which is payment or acceptance of interest fees for loans of money as contradict with the conventional system. While, the science of fund management was to explain the term finance itself. Saving and lending of money sometimes could be related to finance it. To facilitate the lending, borrowing and investment functions under the Islamic finance was based on the risk –sharing basis. Thus, it has allowed market forces to determine the productivity of capital rather than put it in priority as an “interest rate’’ to encourage the speculative use and hoarding of capital and to sabotage the free market mechanism. The Islamic financial system leads to a sustainable economic growth and fair opportunities for all as it’s ensures the efficient utilization and optimal rate of capital formulation. Almost four decades old the Islamic banking and finance field. In late 1940s, Islamic banking starts to develop and in the next two decades, they turn into a model point of yielding which was adopted in the Middle Eastern countries to fulfil their own needs of having their own banks. Some of reputable Islamic banks that came into the 1970s were Islamic Development Bank (IDB) (1975), Dubai Islamic Bank (1975) and Kuwait Finance House (KFH) (1977). In 1980s, the Islamic banking sector surprise the world as three Muslim countries had decided to adapted and transform their economies and financial sector into Islamic point of view, which is Iran, Pakistan and Sudan. While the other Western financial market such as Citibank, HSBC and others has established their own Islamic section or windows to attract others depositors from Middle East and Muslim customers in local markets. By diversifying and continuously improve the products such as Sukuk, Takaful, hedging funds, Mutual funds, private equity and assets management, wealth management, real estate, corporate finance, liquidity management, treasury, derivatives, swaps, future and forward market, Islamic Stock Exchange and Dow Jones Islamic Index is a mechanism or tools used by Islamic banking and finance continuously grows. As we are in the 20th century, the purpose of this research was to find out how far thus the Islamic banking and finance products has develop in Malaysia as it is well accepted not to Muslim itself but also to other races as well. As to conduct this research, it is hope that the Islamic banking and finance products could be well known and developed to all and efficiently adopted in Malaysia banking sectors.